ENTREPRENEURIAL ORIENTATION IN THE RELATIONSHIP BETWEEN RISK TAKING AND MSME PERFORMANCE - Yadewani, Dorris; Wijaya, Reni (Universitas Riau Kepulauan, 2025)
This study aims to analyze the effect of risk-taking on SME performance with entrepreneurial orientation as a mediating variable. The population of this research consists of SME actors in Padang, with 60 respondents selected using purposive sampling. Data were analyzed using multiple linear regression and the Sobel test to examine the mediating effect. The results show that risk-taking has a positive influence on SME performance, while entrepreneurial orientation also contributes to performance improvement, although in a smaller proportion. Furthermore, entrepreneurial orientation is proven to mediate the relationship between risk-taking and SME performance, indicating its significant role in strengthening the positive impact of risk-taking on business outcomes. These findings imply that developing entrepreneurial orientation among SMEs is essential to optimize risk-taking behavior as a strategy for enhancing competitiveness and achieving sustainable performance